Pembibitan Jiwa Edupreneurship Pada Guru Madrasah Ibtidaiyah Se Kota Batu Melalui Pelatihan Digital Content Creator - Bashith, Abdul; Nasith, Ali; Hidayah, Rifa; Adji, Waluyo Satrio; Amin, Saiful; Mashuri, Ali; Bahrul Ulum, mukhammad; Putra Pratama, Erdin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study was to determine the activities of planning, implementing, observing, and evaluating in nurturing the spirit of edupreneurship in non-permanent teachers at Madrasah Ibtidaiyah in other Batu City through digital content creator training. The method used is PAR (Participatory Action Research). The PAR method involves researchers and communities working together to identify and resolve problems. Activities at this planning stage, namely the preparation of training activity materials. This activity was carried out in the form of a focus group discussion (FGD) involving the chairman of the Batu City KKMI, representatives of teachers, researchers, and resource persons. The agreed FGD results. The action stage is actualized with a training event that is divided into two mirrors. First, making learning videos. Both uploads. Observations, observations that have been made in the training obtained weaknesses and strengths experienced by researchers, coordinators, and teachers both in terms of attitudes and obstacles in training such as facilities and infrastructure. Reflection and evaluation activities are in the form of conveying supporting and inhibiting factors during the training activities and giving appreciation to participants